Litter and nutrient accumulation in areas with different methodologies of forest restoration - Klippel, Valéria Hollunder; Pezzopane, José Eduardo Macedo; Caldeira, Marcos Vinicius Winckler; da Silva, Gilson Fernandes; Castro, Kallil Chaves (Comunicata Scientiae, 2016)
The objective of this study was to evaluate the forest restoration indexes (chemical soil attributes, accumulated litter and nutrients content) in different methods of forest restoration of an Atlantic Forest Tableland in Linhares, ES, Brazil. The experiment was installed on August, 2007 in a randomized block design with four treatments and three repetitions: T1 (Control)- only the control of leaf-cutting ants, T2: manual selective mowing, selective chemical weed control, control of ants and herbicide-tolerant species; T3: same for treatment 2, but planting pioneer species from the Atlantic Forest spaced 5x5m, interleaving, in the same spacing, the seeding of Sesbania grandiflora ; T4: same for treatment 2, but planting 54 species from the Atlantic Forest spaced 3x3m. The average total production of litter, accumulated from the four different methodologies for forest restoration was 7.4 Mg ha-1. The K content was the only with statistic significant difference (higher for T1 and lower for T4). For micronutrients, no statistical difference between treatments was observed when the accumulatedlitter was evacuated. The evaluation of soil chemical properties and accumulated litter, in general, were not influenced by the used methodologies for forest restoration, which can be attributed to the short time of implementation of the treatments.